Sistem Penjadwalan Maintenance AC Berbasis Mobile Menggunakan Algoritma Genetika Pada Hotel Nusa Dua Convention Center - I Putu Gd Abdi Sudiatmika; Komang Hari Santhi Dewi; Mafrul Zaenal Alfian (Journal of Information System Research (JOSH), 2022)
Scheduling is the most important thing in Instasi, at the Bali Nusa Dua Convention Center hotel. In this system AC maintenance scheduling is intended for staff technicians at BNDCC hotels. In BNDCC, scheduling still uses a manual system using bookkeeping so that ac maintenance scheduling takes a long time and the resulting schedule information is less effective because the process tends to take a long time and the information generated is less accurate. The purpose of this study is to apply a genetic algorithm to solve optimization problems in scheduling ac maintenance. Genetic algorithms present candidate solutions randomly, then evaluate using the fitness function and then do a selection, then cross-move and mutase. After a few generations the genetic algorithm produces the best schedule. Scheduling In making this scheduling system uses the development of the waterfall method and is designed using the Unified Modeling Language (UML) with the Hypertext Prepprocessing (php) programming language and MySQL as a database. In the scheduling system it has a generate function that generates an AC maintenance schedule automatically. With the scheduling system, the scheduling process can be done quickly and effectively. Besides the scheduling system that is built to display the overall schedule, namely Day, Time, Room, Technician and Job. At the final stage of testing, the system is tested using the blackbox testing method and all tests performed have obtained the appropriate results.